Evaluation procedures for colapsible soils through correlation between edometric tests and spt tests - da SILVEIRA, Paulo Edison Martins [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP] (My University, 2021)
The term collapsibility of soils is not always understood, since engineering projects rarely take into account the effects caused by the phenomenon, which is responsible for several problems in earthmoving services, channels, slope cuts and other types of works. The occurrence of collapse is associated with a high void index and a natural humidity lower than that of saturation. Generally, macroporous and lateritic microaggregated superficial soils, pedologically developed, present some collapsiveness. The research criteria for these soils are based on characterization tests, edometric tests and field tests, such as the SPT test. This work presents procedures for assessing the occurrence of soil collapsibility by the correlation between analysis of the results of the edometric tests and SPT tests. The methodology adopted was the excavation of a trench with the collection of undisturbed samples to perform edometric tests and the execution of a percussion drilling in order to correlate the indices of resistance to soil penetration (N-SPT) and the edometric results. The results showed that, considering the restrictions on the use of soil penetration resistance indices (N-SPT) for the purpose of assessing the susceptibility to the phenomenon of soil collapse, when these are corroborated with the collapse rates determined by edometric tests, they attest the susceptibility preliminarily determined by the investigative criteria based on the geotechnical characterization (physical indices, granulometric aspects, consistency indices) and on the compaction of these materials.
Procedimentos de avaliação de solos colapsíveis por meio de correlação entre ensaios edométricos e ensaios spt
Keywords: Assessment of collapsible soils; Collapsible soil